(untitled) (Docentes 2.0 Journal, 2024)
Culture shapes the identity of nations; it is part of our being when we adapt to societies that are inclusive of diversity. The objective of the investigative work was to dimension the transversal intercultural context with education to reconnect inclusive societies supported by the right of freedom of choice. This essay was framed using the inductive method, hermeneutic paradigm, qualitative interpretive approach, and topical narrative design. Interculturality as communication represents a challenge in coexistence, interaction, and relationships to prevail over inequality and horizontality with respect. It means guiding the democratization of knowledge toward developing local, regional, and spheres. In this regard, the reflections argue that international discourse influences the content priorities of inclusion and education in postmodern societies. This means intercultural education in the complex learning environment converges with critical multiculturalism in its inclination toward l and the global community.